Oscilador harmônico num meio elástico com uma deslocação espiral - Maia, Anderson Vinícius Dantas Marques (2018)
In this work, it is analysed the spectrum of energy of a spinless quantum particle subject to a two-dimensional harmonic oscillator in an elastic medium that possesses a spiral dislocation (a linear topological defect). It is also analysed the efects of this topological defect on the confinement to a hard-wall confining potential. Based on the diferential geometry, the information about the topological defect is introduced into the Schrödinger equation via the Laplace-Beltrami operator. Then, it is shown that analytical solutions to the Schrödinger equation can be obtained and discussed the topological effects of the energy levels.